Inattentional Blindness in Biology - Board, Editorial (Organisms. Journal of Biological Sciences, 2021)
Exceptional responders (ER) are those cancer "patients whom a complete or partial response was expected in less than 10% of similarly treated patients or whose duration of response lasted three times the published median or longer” (Wheeler et al. 2020). This represents a puzzling case for mainstream cancer research. The Tissue Organization Field Theory (TOFT) could instead explain it, by positing that the initiation and progression of cancer is due to the disruption of the normal interaction of cells and tissues, and that proliferation is the default state of all cells (Sonnenschein & Soto 2020). An increasing number of observations suggest that cancer initiation and its progression, or regression, are not primarily caused by intracellular processes but should be considered, instead, relational phenomena occurring in tissues, involving the entire organism and its environment.